Sexually Transmitted Infections Among HIV-Infected Individuals in the District of Columbia and Estimated HIV Transmission Risk: Data From the DC Cohort. (24th January 2018) - Lucar, Jose; Hart, Rachel; Rayeed, Nabil; Terzian, Arpi; Weintrob, Amy; Siegel, Marc; Parenti, David M; Squires, Leah E; Williams, Rush; Castel, Amanda D; Benator, Debra A
Abstract: Background: Washington, DC, has one of the highest rates of HIV infection in the United States. Sexual intercourse is the leading mode of HIV transmission, and sexually transmitted infections (STIs) are a risk factor for HIV acquisition and transmission. Methods: We evaluated the incidence and demographic factors associated with chlamydia, gonorrhea, and syphilis among HIV-infected persons enrolled at 13 DC Cohort sites from 2011 to 2015. Using Poisson regression, we assessed covariates of risk for incident STIs. We also examined HIV viral loads (VLs) at the time of STI diagnosis as a proxy for HIV transmission risk. Results: Six point seven percent (451/6672) developed an incident STI during a median follow-up of 32.5 months (4% chlamydia, 3% gonorrhea, 2% syphilis); 30% of participants had 2 or more STI episodes. The incidence rate of any STIs was 3.8 cases per 100 person-years (95% confidence interval [CI], 3.5–4.1); age 18–34 years, 10.8 (95% CI, 9.7–12.0); transgender women, 9.9 (95% CI, 6.9–14.0); Hispanics, 9.2 (95% CI, 7.2–11.8); and men who have sex with men (MSM), 7.7 (95% CI, 7.1–8.4). Multivariate Poisson regression showed younger age, Hispanic ethnicity, MSM risk, and higher nadir CD4 counts to be strongly associated with STIs. Among those with an STI, 41.8% had a detectable VL within 1 month of STI diagnosis, and 14.6% had a VL ≥1500 copies/mL. Conclusions: STIs are highly prevalent among HIV-infected persons receiving care in DC. HIV transmission risk is considerable at the time of STI diagnosis. Interventions toward risk reduction, antiretroviral therapy adherence, and HIV virologic suppression are critical at the time of STI evaluation.